2022
DOI: 10.3389/fvets.2022.944821
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk factors in puppies and kittens for developing chronic disorders in adulthood: A call for research on developmental programming

Abstract: Many dogs and cats are affected by chronic diseases that significantly impact their health and welfare and relationships with humans. Some of these diseases can be challenging to treat, and a better understanding of early-life risk factors for diseases occurring in adulthood is key to improving preventive veterinary care and husbandry practices. This article reviews early-life risk factors for obesity and chronic enteropathy, and for chronic behavioral problems, which can also be intractable with life-changing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 219 publications
1
6
0
1
Order By: Relevance
“…This suggests that birth weight is not only related to very early neonatal mortality but can also impact later life, in this case, with a midterm impact. This result is in line with that of Gaillard et al [ 48 ] and Mugnier et al [ 49 ], suggesting long-term consequences of reduced intrauterine growth in the canine species.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that birth weight is not only related to very early neonatal mortality but can also impact later life, in this case, with a midterm impact. This result is in line with that of Gaillard et al [ 48 ] and Mugnier et al [ 49 ], suggesting long-term consequences of reduced intrauterine growth in the canine species.…”
Section: Discussionsupporting
confidence: 93%
“…[56][57][58][59][60] This hypothesis identifies that preventing and treating childhood obesity is essential to reducing obesity risks and prevalence in adulthood. These studies were conducted in humans; however, similar results have been observed in cats, 8,24,55,[61][62][63] such that rapid growth in kittens was a predictor of obesity in the adult life stage. 24 Feline growth can be broken down into five stages (Table 2).…”
Section: Growth As a Target Population For Obesity Preventionmentioning
confidence: 57%
“…Early development has previously been identified as a key life stage for preventing various diseases and disorders, such as obesity, in cats. 55 In humans, poor nutrition during fetal development and childhood overweight or obese condition are associated with health complications into adulthood, such as obesity and diabetes mellitus; this is known as the Barker hypothesis. [56][57][58][59][60] This hypothesis identifies that preventing and treating childhood obesity is essential to reducing obesity risks and prevalence in adulthood.…”
Section: Growth As a Target Population For Obesity Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the differences with mouse, rabbit and human, evidence of maternal programming in the canine species is lacking [ 41 ]. This work provides the demonstration of an association between birth weight (endpoint of embryofetal growth) and adiposity at adulthood in dogs.…”
Section: Discussionmentioning
confidence: 99%